2018
DOI: 10.1021/acscatal.7b04369
|View full text |Cite
|
Sign up to set email alerts
|

A Whole Cell E. coli Display Platform for Artificial Metalloenzymes: Poly(phenylacetylene) Production with a Rhodium–Nitrobindin Metalloprotein

Abstract: Whole cell catalysis is, in many cases, a prerequisite for the cost-effective production of chemicals by biotechnological means. Synthetic metal catalysts for bioorthogonal reactions can be inactivated within cells due to abundant thiol derivatives. Here, a cell surface display-based whole cell biohybrid catalyst system (termed ArMt bugs) is reported as a generally applicable platform to unify cost-effective whole cell catalysis with biohybrid catalysis. An inactivated esterase autotransporter is employed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 29 publications
1
67
0
3
Order By: Relevance
“…[29] Theinitially formed white suspension and slow color change to dark-brown may indicate the intermediacyo fa lkynyl manganese oligomers under catalytic conditions.T he reaction of Mn(hmds) 2 with phenylacetylene (2 equiv;or2 with 1equiv phenylacetylene) presumably gave rise to the formation of heterogeneous Mn 0 species upon deprotonation, coordination, and reductive elimination of 1,4-diphenylbutadiyne.W er ecently reported the efficient manganese-catalyzed hydrogenation of alkenes, alkynes,and imines under related mild conditions. Ther emaining substrate presumably underwent polymerization, which resulted in an orange solid with the characteristic broad 1 Hresonances at 5.5-8 ppm.…”
mentioning
confidence: 99%
“…[29] Theinitially formed white suspension and slow color change to dark-brown may indicate the intermediacyo fa lkynyl manganese oligomers under catalytic conditions.T he reaction of Mn(hmds) 2 with phenylacetylene (2 equiv;or2 with 1equiv phenylacetylene) presumably gave rise to the formation of heterogeneous Mn 0 species upon deprotonation, coordination, and reductive elimination of 1,4-diphenylbutadiyne.W er ecently reported the efficient manganese-catalyzed hydrogenation of alkenes, alkynes,and imines under related mild conditions. Ther emaining substrate presumably underwent polymerization, which resulted in an orange solid with the characteristic broad 1 Hresonances at 5.5-8 ppm.…”
mentioning
confidence: 99%
“…3, a nitrobindin variant was fused with an inactivated esterase autotransporter (EstA) in order to be shuttled to microbial cell surfaces. 59) In this case, construction of the rhodium-based ArM was done through covalent linkage between Cys96 of the protein and a Rh(III)-maleimide complex. Subsequent studies then showed that phenylacetylene could be polymerized to PPA (also known as poly(phenylacetylene)) with high favorability to the trans isomer at a high turnover (39 # 10 6 per cell) on E. coli surfaces.…”
Section: Arms With Abiotic Transition Metalsmentioning
confidence: 99%
“…Ther emaining substrate presumably underwent polymerization, which resulted in an orange solid with the characteristic broad 1 Hresonances at 5.5-8 ppm. [29] Theinitially formed white suspension and slow color change to dark-brown may indicate the intermediacyo fa lkynyl manganese oligomers under catalytic conditions.T he reaction of Mn(hmds) 2 with phenylacetylene (2 equiv;or2 with 1equiv phenylacetylene) presumably gave rise to the formation of heterogeneous Mn 0 species upon deprotonation, coordination, and reductive elimination of 1,4-diphenylbutadiyne.W er ecently reported the efficient manganese-catalyzed hydrogenation of alkenes, alkynes,and imines under related mild conditions. [10] Va rious Mn catalysts have recently been reported for the hydrogenation of carbonyl derivatives, [30,31] whereas olefin hydrogenation reactions are very rare.…”
Section: Angewandte Chemiementioning
confidence: 99%